Feminist Experiences (RLE Feminist Theory) : the Women's Movement in Four Cultures. - Bassnett, Susan (Routledge library editions. Feminist theory., 2012)
The Women's Movement is usually referred to as if it were a constant, global phenomenon. There are women's movements in Europe, North and South America, Africa, the Middle East, India, Japan and Australia, and many women and men assume that they are regional manifestations of the same thing, and share a common core. Susan Bassnett has lived and been involved in the struggles of the women's movement in the United States, Italy and the United Kingdom, and has had extensive contacts with feminists in the German Democratic Republic. On the basis of her personal experiences and study of women's hist.